What Makes a Nobel Prize Innovator? Early Growth Experiences and Personality Traits - Zheng, Linlin; Wu, Yenchun Jim; Li, Yuyi; Ye, Di; Li, Wenzhuo (Frontiers in Psychology, 2022)
The original innovation talents and their achievements promote the development of natural science and are regarded as a symbol of the national comprehensive power. This paper explored the process which causes original innovation talents’ personality, used Fuzzy-Set Qualitative Comparative Analysis and explored the linkage between configurations made up of early growth experiences and personality. We took Nobel Prize winners as samples and discovered that high responsibility was inspired by high family democracy driving, high family size driving, high family function driving, and high teaching democracy driving; high extroversion was inspired by high family size driving, high family democracy driving, and high family status driving; high openness was inspired by high family status driving, high family democracy driving, high family size driving, both high open teaching and educational level driving as well as high peer support driving; high or non-high family status brought high extroversion or openness; non-high teacher accomplishments and teacher-student relationships produced high openness; non-high extroversion came with non-high teacher-student relationship. We proposed strategies for strengthening the positive effects or avoiding the negative effects of early growing-up experiences on personality.